Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.is.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Improving the usability of standard schemas

Abstract: Due to the development of XML and other data models such as OWL and RDF, sharing data is an increasingly common task since these data models allow simple syntactic translation of data between applications. However, in order for data to be shared semantically, there must be a way to ensure that concepts are the same. One approach is to employ commonly used schemas -called standard schemas -which help guarantee that syntactically identical objects have semantically similar meanings. As a result of the spread of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Bring into this complexity the number of different aspects of our target domain that need to be represented (Strömbäck et al found 85 different schemas within the sub-domain of systems biology alone[ 35 ]), and there is immediately a requirement for either schema standardization, or schema mapping to facilitate interoperability. Schema standardization is "prohibitively time-consuming" [ 36 ], and though there have been numerous attempts to automate schema mapping - that is, the ability for two schema to exchange data, as would be required to automate the interaction between arbitrary Web services - none have proven reliable in an open-Web situation [ 37 ]. Automated Schema mapping is likely an AI-complete problem since it requires the mapping of arbitrarily chosen natural-language labels (XML tags) to one another based on the semantics of either the tag or its child-content.…”
Section: Discussionmentioning
confidence: 99%
“…Bring into this complexity the number of different aspects of our target domain that need to be represented (Strömbäck et al found 85 different schemas within the sub-domain of systems biology alone[ 35 ]), and there is immediately a requirement for either schema standardization, or schema mapping to facilitate interoperability. Schema standardization is "prohibitively time-consuming" [ 36 ], and though there have been numerous attempts to automate schema mapping - that is, the ability for two schema to exchange data, as would be required to automate the interaction between arbitrary Web services - none have proven reliable in an open-Web situation [ 37 ]. Automated Schema mapping is likely an AI-complete problem since it requires the mapping of arbitrarily chosen natural-language labels (XML tags) to one another based on the semantics of either the tag or its child-content.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation is not the only field where this problem occurs. Recent reports from civil engineering and architecture such as by Zhang et al [2011] are based on the fact that common schemas across a domain are not possible. Similar reports were published earlier in the cultural heritage sector (e.g.…”
Section: Cidoc-crm Aat and Rdf [Heading]mentioning
confidence: 99%
“…Even with the evolution of BIM, embodying parametric objects governed by rules of geometry, attributes and relations; this vision is yet to be fully realized. The inclusion and accessibility of other design information such as cost estimation, selection of construction methods, construction scheduling, productivity analysis and project management associated with various construction practitioners still need tackling [8].…”
Section: Introductionmentioning
confidence: 99%